COMBINATION OF LINGUADIDACTICS AND INTERACTIVE METHODS (Konferensiyalar | Conferences, 2024)
The purpose of the article is to show developing the lingo didactic foundations of language teaching and ways to solve problems that arise in practice. The tasks are to reveal the relevance of the use of interactive methods, to analyze the specific f eatures of language teaching, to demonstrate the effectiveness of the combined use of language didactics and interactive methods.